X-ray diffraction analysis of cubic zincblende III-nitrides. (26th September 2017) - Frentrup, Martin; Lee, Lok Yi; Sahonta, Suman-Lata; Kappers, Menno J; Massabuau, Fabien; Gupta, Priti; Oliver, Rachel A; Humphreys, Colin J; Wallis, David J
Abstract: Solving the green gap problem is a key challenge for the development of future LED-based light systems. A promising approach to achieve higher LED efficiencies in the green spectral region is the growth of III-nitrides in the cubic zincblende phase. However, the metastability of zincblende GaN along with the crystal growth process often lead to a phase mixture with the wurtzite phase, high mosaicity, high densities of extended defects and point defects, and strain, which can all impair the performance of light emitting devices. X-ray diffraction (XRD) is the main characterization technique to analyze these device-relevant structural properties, as it is very cheap in comparison to other techniques and enables fast feedback times. In this review, we will describe and apply various XRD techniques to identify the phase purity in predominantly zincblende GaN thin films, to analyze their mosaicity, strain state, and wafer curvature. The different techniques will be illustrated on samples grown by metalorganic vapor phase epitaxy on pieces of 4″ SiC/Si wafers. We will discuss possible issues, which may arise during experimentation, and provide a critical view on the common theories.